Antibiotics Utilization for Community Acquired Pneumonia in a Community Hospital Emergency Department. (February 2022) - Yu, Jessica; Wang, Gillian; Davidson, Ann; Chow, Ivy; Chiu, Ada
Background: A local health authority in Canada implemented its own Antimicrobial Stewardship Program (ASP) which provide guidelines to clinicians to utilize when treating infectious diseases such as community-acquired pneumonia (CAP). Objectives: The primary objective is to describe antibiotic usage patterns at the community hospital's emergency department (ED) and to analyze the patterns in relation to ASP goals of reducing risk of infections, adverse drug events and antibiotic resistance, and to identify potential areas of improvement. Methods: This retrospective chart review included 156 adult patients with a diagnosis of CAP admitted to a community hospital ED from December 1, 2015 to November 30, 2016. Results: 50.6% patients were prescribed moxifloxacin across all severity of CAP patients. Low and moderate severity CAP patients were most often prescribed antibiotic duration > 7 days. In low, moderate and high severity CAP patients who were treated using ceftriaxone, 100%, 88.9% and 66.6% patients were treated with ceftriaxone 2000 mg daily respectively. Conclusions: Antibiotic prescribing patterns suggest fluoroquinolones were frequently being over-prescribed, ceftriaxone dosages were often too high, and duration of antibiotics for low and moderate severity CAP were too long. More efforts are needed to promote appropriate antibiotic usage and optimize patient care.